2017
DOI: 10.1021/acsami.7b15601
|View full text |Cite
|
Sign up to set email alerts
|

Relating Structure to Efficiency in Surfactant-Free Polymer/Fullerene Nanoparticle-Based Organic Solar Cells

Abstract: Nanoparticle dispersions open up an ecofriendly route toward printable organic solar cells. They can be formed from a variety of organic semiconductors by using miniemulsions that employ surfactants to stabilize the nanoparticles in dispersion and to prevent aggregation. However, whenever surfactant-based nanoparticle dispersions have been used to fabricate solar cells, the reported performances remain moderate. In contrast, solar cells from nanoparticle dispersions formed by precipitation (without surfactants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
(91 reference statements)
1
28
0
Order By: Relevance
“…The phase separation into NPs has been studied by SANS with contrast variation for composite P3HT:ICBA NPs prepared by nanoprecipitation from chloroform solution into methanol. 46 It was confirmed that the two materials were homogeneously distributed in the NPs having a diameter of around 100 nm. By SANS, it was not possible to observe phase separation down to the 10 nm size observable by this technique.…”
Section: Nanoprecipitationmentioning
confidence: 87%
“…The phase separation into NPs has been studied by SANS with contrast variation for composite P3HT:ICBA NPs prepared by nanoprecipitation from chloroform solution into methanol. 46 It was confirmed that the two materials were homogeneously distributed in the NPs having a diameter of around 100 nm. By SANS, it was not possible to observe phase separation down to the 10 nm size observable by this technique.…”
Section: Nanoprecipitationmentioning
confidence: 87%
“…We note that the nanoprecipitation method, compared to the miniemulsion method, has been previously reported to produce nanoparticles with a predominantly uniform phase separation. 42,[68][69][70] Our study constitutes the first report of the nanoscale morphology of P3HT:eh-IDTBR nanoparticles prepared from both the nanoprecipitation and the miniemulsion method, both being core-shell in nature. It is possible that for the nanoprecipitated P3HT:eh-IDTBR nanoparticles a uniform phase separation formed inititally, but then self-assembly to a core-shell structure occurred during the 3 hour 60 1C THF solvent removal step (from the continuous aqueous phase), a temperature above the reported T g of P3HT.…”
Section: Nanoparticle Synthesis and Electron Microscopymentioning
confidence: 87%
“…and Gärtner et al . both argued that better mixing of P3HT and PC 61 BM or ICBA can be achieved in NPs prepared using reprecipitation compared to miniemulsion . The as cast P3HT : ICBA NP PSCs have low PCEs of 0.1 % which can be gradually increased to 1.2 %, 3.0 %, 3.7 % and 3.9 % by applying thermal annealing at 100 °C, 150 °C, 180 °C and 200 °C, respectively.…”
Section: Eco‐friendly and Sustainable Active Layer Fabrication Processesmentioning
confidence: 99%
“…Schwarz et al and Gärtner et al both argued that better mixing of P3HT and PC 61 BM or ICBA can be achieved in NPs prepared using reprecipitation compared to miniemulsion. [67,68] The as cast P3HT: ICBA NP PSCs have low PCEs of 0.1 % which can be gradually increased to Adapted with permission from, [49] Copyright 2017, Elsevier B.V. (b) Schematic representation of the miniemulsion process. Adapted with permission from, [55] Copyright 2017, American Chemical Society .…”
Section: Can Efficient Pscs Be Produced Using Active Layers Depositedmentioning
confidence: 99%